2015
DOI: 10.1371/journal.pone.0136664
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of High Out of Pocket Spending for HIV Care Leading to Catastrophic Expenditure for Affected Patients in Lao People's Democratic Republic

Abstract: BackgroundThe scaling up of antiviral treatment (ART) coverage in the past decade has increased access to care for numerous people living with HIV/AIDS (PLWHA) in low-resource settings. Out-of-pocket payments (OOPs) represent a barrier for healthcare access, adherence and ART effectiveness, and can be economically catastrophic for PLWHA and their family. We evaluated OOPs of PLWHA attending outpatient and inpatient care units and estimated the financial burden for their households in the Lao People's Democrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
(55 reference statements)
2
22
1
Order By: Relevance
“…In order to access and maintain treatment, patients have to incur many nonmedical costs, including travel costs, meals, accommodation, opportunity costs and other medications. Therefore, even without the need to pay for ART itself, many patients face a significant financial burden just to access and sustain their treatment . Potential solutions to cope with household income to finance health care for poorer households have been explored such as mutual health organizations and microfinancing for health.…”
Section: Discussionmentioning
confidence: 99%
“…In order to access and maintain treatment, patients have to incur many nonmedical costs, including travel costs, meals, accommodation, opportunity costs and other medications. Therefore, even without the need to pay for ART itself, many patients face a significant financial burden just to access and sustain their treatment . Potential solutions to cope with household income to finance health care for poorer households have been explored such as mutual health organizations and microfinancing for health.…”
Section: Discussionmentioning
confidence: 99%
“…The costs incurred often have impoverishing effects on some households and hinder PHI adolescents from getting necessary care [18]. Furthermore, the costs may result in catastrophic health expenses in the context of fragile economic balance and low insurance coverage [19].…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of the world, the poor and disadvantaged still experience significant economic burden from high payments for health care to a lack of trained professionals and limited access to services. Studies in resource‐poor nations have shown that out‐of‐pocket payments for health care and accessing health services significantly impact spending on life's necessities and can thrust families into poverty (Barennes, Frichittavong, Gripenberg, & Koffi, ; Masiye, Kaonga, & Kirigia, ).…”
Section: Introductionmentioning
confidence: 99%